KONTRIBUSI GAYA KEPEMIMPINAN DAN MOTIVASI KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH MENENGAH ATAS KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - FITRIA APRIANA; HASNAH FAIZAH; JIMMI COPRIADY (Universitas Riau, 2017)
The purpose of this research to determine whether there is the contribution of astyle of leadership and motivation the school principal on the performance of junior high schoolteachers kecamatan singingi hilir kabupaten kuantan singingi .Sample in this research using atechnique of sampling probabillity taken as proportionate stratified random sampling by thenumber of some 63 people. Data analysis used in this research the correlation coefficient isproduct moment and correlation analysis. Based on analysis of the data and the testing ofhypotheses consisting of two variables free namely variable style of leadership (x1) and motivationthe school principal (x2) their lack of roots and variable is performance teachers (y). Theresults of the study show their contribution style of leadership (x1) of performance of teachers(y), obtained value koefesien correlation r of 0,719 , with the determination of 0,516 koefesien.To koefesien correlation motivation the school principal (x2) of performance of teachers (y) asmuch as 0,731 with the determination of 0,527 koefesien. Next koefesien correlation togetherbetween contribution style of leadership (x1) and motivation the school principal (x2) ofperformance of teachers (y) as much as 0,758 with koefesien determination of 0,575. Laterretrieved value r square of 0,575 that means that there are contribution style of leadership (x1)and motivation the school principal (x2) of performance of teachers (y) is of 57,5 % , while therest of 42,5 % influenced other variables out variable the treatment. The results of statisticsshows that there is contribution strong and welfare between style of leadership (x1) and motivationthe school principal (x2) of performance of teachers (y) senior high school kecamatan singingihilir kabupaten kuantan singingi.